Dolls of our lives : why we can't quit American Girl - Mahoney, Mary, 1986-; Horrocks, Allison (Feiwel and Friends, 2023)
"Are you a Molly (a patriotic overachiever with a flair for drama)? Felicity (the original horse girl)? Kirsten (a cottagecore fan who seems immune to cholera), Samantha (a savior complex in a sailor suit), or Josefina (who dealt with grief by befriending a baby goat)? Have you ever wondered how Britney Spears or Michelle Kwan would answer that question? And why do we care so much which girl we are? Combining history, travelogue, and memoir, Dolls of Our Lives follows Allison Horrocks and Mary Mahoney on an unforgettable journey to the past as they delve into the origins of this iconic brand. Continuing the conversations that began on their podcast, they set out to answer the lingering questions that keep them up at night. What did American Girl inventor Pleasant Rowland hope to say to children with these dolls? Was girl power something that could be ordered from a catalogue, described by a magazine, or modeled in the plot lines of books? And how - and why - did this brand shape an entire generation? Through interviews with a legion of devoted doll lovers, a field trip to Colonial Williamsburg, a place that inspired Pleasant to create American Girl, and an exploration of their own (complicated) fandom, this is a deep dive into one of the 90s most coveted products - the American Girl doll" --